Deterministic and stochastic effects drive the gut microbial diversity in cucurbit-feeding fruit flies (Diptera, Tephritidae) - Wouter Hendrycks; Nele Mullens; Jackline Bakengesa; Sija Kabota; Jenipher Tairo; Thierry Backeljau; Ramadhani Majubwa; Maulid Mwatawala; Marc De Meyer; Massimiliano Virgilio (PLoS ONE, 2025)
Insect diversity is closely linked to the evolution of phytophagy, with most phytophagous insects showing a strong degree of specialisation for specific host plants. Recent studies suggest that the insect gut microbiome might be crucial in facilitating the dietary (host plant) range. This requires the formation of stable insect-microbiome associations, but it remains largely unclear which processes govern the assembly of insect microbiomes. In this study, we investigated the role of deterministic and stochastic processes in shaping the assembly of the larval microbiome of three tephritid fruit fly species (Dacus bivittatus, D. ciliatus, Zeugodacus cucurbitae). We found that deterministic and stochastic processes play a considerable role in shaping the larval gut microbiome. We also identified 65 microbial ASVs (Amplicon sequence variants) that were associated with these flies, most belonging to the families Enterobacterales, Sphingobacterales, Pseudomonadales and Betaproteobacterales, and speculate about their relationship with cucurbit specialisation. Our data suggest that the larval gut microbiome assembly fits the “microbiome on a leash” model.